Managing Cultural Diversity: The Case of Small & Medium Tourism Enterprises (SMTE) - Sinno Nadine (European Scientific Journal, ESJ, 2017)
For a long time, management has been developing and applying a standardized universal approach with its employees to optimize the operation of companies. This is regardless of the company’s nature and the country where it operates. The failure of certain firms, the increasing globalization of trade, the circulation of goods, and the fast transfer of individuals and information have led to the need to take into account other aspects of management, in particular the intercultural factor. Today, employees from different cultural backgrounds are working as a team in the same company. Nevertheless, differences in understanding values and visions of the world can create intra-team misunderstandings in collaborative work. Managing cultural diversity reduces these misunderstandings so that the benefits of the diversity emerge. Managing cultural diversity means managing opposing opinions, constant contradictions, continuous oppositions, and different perceptions. Furthermore, managing cultural diversity contributes to improving team effectiveness where diverse teams often perform better than homogenous teams in problem solving and complex tasks. Greater diversity leads to innovative, higher-quality decisions, and solutions. This paper sheds light on the importance of cultural diversity among the company’s human resources and the role of cultural intelligence in intercultural management. As part of the research, a study centered on the Lebanese small and medium tourism enterprises (SMTE) was conducted. The results obtained showed a shy diversity management approach in the Lebanese tourism sector due to several factors, namely: the economic instability and lack of training.